Pengembangan Modul Fisika yang Dilengkapi Aplikasi Android pada Materi Medan Magnet di Sekitar Kawat Berarus - Yossa, Yudhistira; Akhlis, Isa (UPEJ Unnes Physics Education Journal, 2021)
The Magnetic Field is an abstract physics material since the object cannot be seen. Learning the media, in the form of modules, equipped with an Android applications, can be used as solutions to improve learning outcomes and visualize magnetic fields. This study aims were to develop a physics module, equipped with an Android application on the magnetic field around the current wire and determine the feasibility of the media being developed. The development model used in this study is the ADDIE model. The product of this research is a physics learning module and an Android application that has been tested on media experts, material experts, and students. For data collection method in this study, were used 3 methods, there are questionnaire, documentation, and interviews. The data processing method used a Likert scale, which consists of a score of 1 to 5. The feasibility test result of module obtained a score of 88.89%, which was categorized as very feasible and Android application obtained a score of 90.53% which was in the very feasible category. Based on the score and category obtained, the physics learning module equipped with an Android application is stated feasible for learning.